Hell's destruction: an exploration of Christ's descent to the Dead - Laufer, Catherine Ella (Ashgate, 2013)
The credal affirmation, `he descended to the dead`, has attracted a plethora of views over the centuries and many Christians today struggle to explain the meaning of these words. This book explores various interpretations of the doctrine of Christ`s descent to the dead, both within particular historical contexts and within contemporary theology. Laufer argues that the descensus clause, Christ`s descent, is integral to Christian faith, specifically to the doctrine of the incarnation. If we are to affirm that, in Christ, God became truly human then that affirmation must include his sharing in the state of being dead that is the ultimate consequence of being human. Laufer concludes that, since the Son has experienced genuine human death and the separation from God which is the essence of hell, there is no longer any human condition from which God is absent, either in this life or in eternity. Christ`s descent means that he is truly `hell`s destruction`. Drawing on a treasure trove of writings from the western theological tradition, including Luther, Calvin, Maurice, Balthasar, Moltmann and others, and attending to historical, theological, exegetical, philosophical and pastoral issues, this book explores an often-ignored doctrine which lies at the core of Christian life, death and faith.